UTILIZATION OF ARDUINO MICROCONTROLLER FOR PRECISE WATER SUPPLY MANAGEMENT TO ENHANCE WATER SPINACH (Ipomoea reptans Poir) GROWTH - Sanjaya, Purba; Widyastuti, R.A Diana; Manik, Tumiar Katarina; Pusvika, Niluh D. (Jurnal Agrotek Tropika, 2025)
In Indonesia, agricultural practices remain largely dependent on traditional methods, particularly in plant care and irrigation management. Such reliance often results in inefficient water use and inconsistent crop yields, underscoring the urgent need for technological innovation in precision agriculture. The integration of affordable microcontroller-based systems offers a practical solution for smallholder farmers to enhance crop productivity and resource efficiency. This study investigates the application of an Arduino UNO microcontroller integrated with a soil moisture sensor for the cultivation of water spinach (Ipomoea reptans Poir) under controlled irrigation conditions. Four soil moisture ranges were tested: 80–100%, 60–80%, 40–60%, and 20–40% of field capacity. The research objectives were to: (i) optimize the operation of the Arduino microcontroller for automated irrigation, (ii) evaluate the effects of different soil moisture levels on water spinach growth, and (iii) determine the optimal moisture range for maximizing growth and yield. The results demonstrate that the Arduino-based system reliably regulated soil moisture according to programmed parameters, enabling precise, automated irrigation aligned with crop water requirements. Growth performance varied significantly across treatments, with plants maintained at 80–100% of field capacity showing the highest growth rate and yield. Notably, water spinach cultivated at 40–60% of field capacity still produced marketable crops, indicating potential water-saving benefits. This research highlights the contribution of low-cost microcontroller technology in advancing precision agriculture for leafy vegetables. It provides practical insights for sustainable irrigation management, offering farmers a feasible pathway to improve productivity while conserving water resources.